Energy Efficiency Policies and the Jevons Paradox - Jaume Freire-González; Ignasi Puig-Ventosa (International Journal of Energy Economics and Policy, 2015)
Energy and climate change policies are often strongly based on achieving energy efficiency targets. These policies are supposed to reduce energy consumption and consequently, associated pollutant emissions, but the Jevons paradox may pose a question mark on this assumption. Rebound effects produced by reduction in costs of energy services have not been generally taken into account in policy making (there is only one known exception). Although there is no scientific consensus about its magnitude, there is consensus about its existence and in acknowledging the harmful effects it has on achieving energy or climate targets. It is necessary to address the rebound effect through behavioral, legal and economic instruments. This paper analyzes the main available policies to minimize the rebound effect in households with special emphasis on economic instruments and, particularly, on energy taxation.
Keywords: 330